2020
DOI: 10.3390/jmse8090716
|View full text |Cite
|
Sign up to set email alerts
|

An Object Model for Seafloor Observatory Sensor Control in the East China Sea

Abstract: Seafloor observatories enable long-term, real-time, and continuous observation that marks a new way for oceanographic measurements. In terms of seafloor observatory research, sensor control is a key issue for the stable and effective operations of functional observatories. In this paper, an object model is proposed to standardize seafloor observatory sensor control and data acquisition. The object model is conceptionally designed as a set of sensor resource objects, based on the attributes and operations of wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 27 publications
0
5
0
Order By: Relevance
“…The high-pressure drop-down brings a large production rate but it causes the subsidence of the seafloor, which increases sand production. 160 That is why Yu et al 161 suggested that NGH production should maintain the minimum seafloor subsidence. So, the sand control design for NGH sediment still needs to consider the natural gas production, especially production rate at different production stages and the production technique.…”
Section: Naturalgasproductionmentioning
confidence: 99%
“…The high-pressure drop-down brings a large production rate but it causes the subsidence of the seafloor, which increases sand production. 160 That is why Yu et al 161 suggested that NGH production should maintain the minimum seafloor subsidence. So, the sand control design for NGH sediment still needs to consider the natural gas production, especially production rate at different production stages and the production technique.…”
Section: Naturalgasproductionmentioning
confidence: 99%
“…As a permanent infrastructure, cabled SON can provide abundant power and broad bandwidth communication [ 1 ]. It enables all-weather, in situ, continuous, real-time, and high-precision observation of the ocean from the sea floor to the sea surface, which is crucial to the development of marine science [ 2 ].…”
Section: Introductionmentioning
confidence: 99%
“…The subsea observation network has received increasing attention worldwide as a new and revolutionary means of ocean observation. The cabled submarine observation network has become a research hotspot in the past decade because of its powerful power supply capacity and ultra-high data transmission rate [1][2][3][4]. The basic idea is to connect the observation instruments and seabed or ocean equipment with the power grid and information network on the land through the submarine cable to extend the land observation to the depth of the ocean.…”
Section: Introductionmentioning
confidence: 99%